The acute inflammatory response to myocardial infarction: imaging with indium-111 labelled autologous neutrophils. Issue 1 (January 1987) - Bell, D; Jackson, M; Millar, A M; Nicoll, J J; Connell, M; Muir, A L
Abstract : The uptake of indium-111 labelled neutrophils was examined in 30 patients with acute myocardial infarction by planar imaging and single photon emission computed tomography. The time from venepuncture to reinjection of the autologous labelled neutrophils was less than 2.5 hours and imaging was carried out 24 hours later. Twenty three patients had a positive uptake of neutrophils in the myocardium and imaging was improved by single photon emission computed tomography. There was a significant difference between the intervals from the onset of chest pain to injection of labelled neutrophils between patients with positive and negative images; early reinjection was more likely to produce a positive image. Indeed, all nine patients reinjected within 18 hours of the onset of symptoms had positive images. The results suggest that the stimulus for activation and migration of neutrophils is transient; this is an important factor if neutrophil release products play a role in cell damage after coronary occlusion.